Genetic relatedness of Burkholderia contaminans clinical isolates from cystic fibrosis and non-cystic fibrosis patients in Argentina - Cipolla, Lucia (2022)
Introduction: The Burkholderia cepacia complex (BCC) bacteria are opportunistic pathogens that cause nosocomial infections and are especially dangerous for cystic fibrosis (CF) patients. Burkholderia contaminans is an emerging BCC species isolated from CF patients that also occurs as a contaminant in pharmaceutical and personal care products, sometimes linking it with outbreaks. Methodology: A total of 55 B. contaminans isolates from CF and non-CF patients in Argentina were identified by recA sequencing and MALDI TOF MS. A standardized Pulsed Field Gel Electrophoresis (PFGE) protocol was set up in order to assess genetic diversity, outbreak investigations, and possible clone persistence. Results: All isolates were identified as B. contaminans by both MALDI-TOF MS and recA sequence analysis. PFGE has enabled us to compare and determine the genetic relationship between B. contaminans isolates. Isolates were distributed in different PFGE clusters with evidence of the presence and persistence of a clone, over a period of 3 years, in the same hospital. This large hospital outbreak involved CF and non-CF patients. Moreover, PFGE results showed a good correlation between sporadic or outbreak-related isolates and the available epidemiological information. Conclusions: These findings highlight the importance of B. contaminans in Argentina and provide evidence for encouraging the surveillance of highly transmissible clones. The study also contributes to global knowledge about B. contaminans infections.